STUDI TINGKAT PENGETAHUAN MASYARAKAT DESA SANREGO KECAMATAN KAHU KABUPATEN BONE TERHADAP BAHAYA PENGGUNAAN KRIM PEMUTIH - Yusriyani Yusriyani; Sukirawati Sukirawati (Jurnal Kesehatan Yamasi Makassar, 2022)
Has conducted research in the Village District of Kahu Sanrego Bone district in August 2015 about the dangers of using a whitening cream that aims to measure the level of public knowledge Sanrego Village District of Kahu Bone regency against the dangers of using a whitening cream. This research is a descriptive study with data collection using a questionnaire with 90 respondents were found for Â± 1 month by accidental sampling technique. Data obtained dipersentase and categorized, ie when 0% -33% lower mean knowledge,> 33% -66% means knowledge being and> 66% -100% means higher knowledge. The result showed the level of public knowledge Sanrego Village District of Kahu Bone regency against the dangers of using a whitening cream in medium category with a percentage score of 44.37%.